TRIBAL PLANTS AND THEIR INBORN ANTIMICROBIAL ACTIVITIES - L, Anitha Jegadeeshwari; N, Dharathi; D, Vidhya Lakshmi; E, Vasanth Kumar; N, Nagendra Gandhi (Asian Journal of Pharmaceutical and Clinical Research, 2017)
The importance of medicinal plants in traditional health-care practices provides clues to new areas of research and in the biodiversity of conservation. Right from the beginning, the documentation of traditional knowledge, especially on the medicinal uses of plants, has provided many important drugs for the modern day. Even today, this area holds much more hidden treasure as almost 80% of the human population in developing countries depend on plant resources for health care. Keeping this in view, the present study was initiated to document the traditionally used tribal plants and their inborn antimicrobial activity which is enhanced on the synthesis of noble metal nanoparticles.